The comparative osteology of the petrotympanic complex (ear region) of extant baleen whales (Cetacea: Mysticeti). - Eric G Ekdale (Public Library of Science (PLoS), 2011)
Background Anatomical comparisons of the ear region of baleen whales (Mysticeti) are provided through detailed osteological descriptions and high-resolution photographs of the petrotympanic complex (tympanic bulla and petrosal bone) of all extant species of mysticete cetaceans. Salient morphological features are illustrated and identified, including overall shape of the bulla, size of the conical process of the bulla, morphology of the promontorium, and the size and shape of the anterior process of the petrosal. We place our comparative osteological observations into a phylogenetic context in order to initiate an exploration into petrotympanic evolution within Mysticeti. Principal findings The morphology of the petrotympanic complex is diagnostic for individual species of baleen whale (e.g., sigmoid and conical processes positioned at midline of bulla in Balaenoptera musculus; confluence of fenestra cochleae and perilymphatic foramen in Eschrichtius robustus), and several mysticete clades are united by derived characteristics. Balaenids and neobalaenids share derived features of the bulla, such as a rhomboid shape and a reduced anterior lobe (swelling) in ventral aspect, and eschrichtiids share derived morphologies of the petrosal with balaenopterids, including loss of a medial promontory groove and dorsomedial elongation of the promontorium. Monophyly of Balaenoidea (Balaenidae and Neobalaenidae) and Balaenopteroidea (Balaenopteridae and Eschrichtiidae) was recovered in phylogenetic analyses utilizing data exclusively from the petrotympanic complex. Significance This study fills a major gap in our knowledge of the complex structures of the mysticete petrotympanic complex, which is an important anatomical region for the interpretation of the evolutionary history of mammals. In addition, we introduce a novel body of phylogenetically informative characters from the ear region of mysticetes. Our detailed anatomical descriptions, illustrations, and comparisons provide valuable data for current and future studies on the phylogenetic relationships, evolution, and auditory physiology of mysticetes and other cetaceans throughout Earth's history.